Levantamento de afecções orais em espécies silvestres mantidas em cativeiro no zoológico da Universidade Federal de Mato Grosso - Andrade, Paula Márcia Marques de Campos (2013)
The control of oral lesions contributes to the health, survival and well-being of captive animals, this study aimed to investigate the occurrence of oral diseases in wild animals kept in the zoo UFMT . We evaluated 32 oral cavities of 11 different species in the period July 2012 to April 2013, being 12 coatis (Nasua Nasua) , 3 raccoons (Procyon cancrivorus) , 2 maned wolves (Chrysocyon brachyurus) , 6 crab-eating fox (Cerdocyon thous), 1 fox (Pseudalopex vetulus), 3 ocelot (Leopardus pardalis), 1 cougar (Puma concolor) , 3 wild cats (Puma yaguaroundi , Leopardus wiedii , Leopardus colocolo) and 1 tayra (Eira barbara). The most frequent lesions were dental absences 22/32 (68.8%), dental fractures 21/32 (65.6%) and tooth wear 20/32 (62.5%). The greater the age, the greater the number and severity of lesions. Were also observed periodontal disease, caries, foreign body, orofacial fistula, and hyperplasia abrasions in soft tissues. The conclusion is thus the need to develop environmental enrichment and other management practices and improvements in enclosures to reduce the stress of the captive animals, once these are predisposing factors for dental traumatic injury, and the maintenance of the diet supplied, which contributes to the low incidence of periodontal disease